ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERSAINGAN USAHA AIR MINUM ISI ULANG DI KOTA TIMIKA - Lia Via Alfionita Leisubun; Rulan L. Manduapessy (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2026)
This study aims to determine the factors that influence competition among refillable drinking water depots in Mimika Regency. The research method used in this study is descriptive, with data collection techniques including observation, interviews, and questionnaires. To identify the factors that influence competition among refillable drinking water depots in Mimika Regency, the data analysis instrument used is PCA factor analysis. The results of the study show that there are factors that influence competition among refillable drinking water depots in Timika City.